A REAPPRAISAL OF REGIONAL SURFACE WAVE TOMOGRAPHY - Kennett B.L.N.; Yoshizawa K. (My University, 2002)
A three-stage inversion scheme for surface wave tomography working with multimode phase dispersion as a function of frequency provides a means of combining a wide range of data in a common framework. The phase average approximation is applied directly to phase slowness and there is no need to invoke perturbation arguments for the interpretation of path-averaged velocity models derived from waveform inversion of surface waves. By treating such wave speed profiles as summaries of path specific dispersion behaviour it is possible not only to combine results from different style of inversion but also to provide maximum exploitation of Love and Rayleigh wave information. Inversions of all suitable waveforms can be undertaken in terms of isotropic models. Dispersion information from all paths is combined to form multimode phase speed distributions as a function of frequency in linearized inversion which takes account of path bending and finite frequency effects. The final inversion for 3-D wave speed structure is based on a cellular inversion of the multimode frequency dispersion including angular effects in terms of a local stratified model including anisotropy. The smoothing from inclusion of finite frequency effects and damping of the linearized inversion for the phase speed distributions will control the smoothness of the 3-D shear wave speed model.
Keywords: DISPERSION; MULTIMODE ANALYSIS; SURFACE WAVE TOMOGRAPHY; WAVEFORM INVERSION